DIMENSI KEKUASAAN DALAM EKONOMI - Damayanti, Christy (Universitas Slamet Riyadi, 2009)
Abstract Political economy approach to place the state as a formal institution that rests on the concept of values, shared interests, and power, actively participates in economic activities. The state is managing the resources of power, and power relations within the state will determine the relations and economic distribution. Dimension of state-owned power used to perform three functions in the economy, namely economic activity regulation, income redistribution, and procurement of commodity goods and public services both tangible or intangible. State and non-state economic actors affect each other, with the state power system determine patterns of economic activity, while the economy determine the redistribution of power and wealth. Keywords: power, economic activity, political economy